Are parenting interventions effective in improving parental functioning in parents of children with ASD?: a meta-analysis - Hemdi, A.; Daley, David (International Journal of Academic Scientific Research, 2017)
This meta-analysis (M-A) evaluated the effectiveness of parenting interventions on parental functioning in parents of children with autism spectrum disorder (ASD). Electronic searches of Pub Med, Psyc INFO, and Web of Knowledge databases identified controlled and pre to post trials evaluating the effectiveness of parenting interventions on parental functioning, Eleven studies that met the inclusion criteria were included in this M-A. A random effect M-A estimated pooled standard mean difference (SMD) for parenting interventions on measures of stress, sense of competence, parenting practices, depression and anxiety. Analyses revealed medium but significant effects of interventions on parents’ stress pre-post intervention. This effect remained medium and significant when controlled studies were analysed and also following sensitivity analyses removing non-randomised trials. Moreover, the analyses showed a large and significant effect of interventions on parental sense of competence pre-post intervention. The effect decreased to medium and significant for sense of competence when controlled studies were analysed and remained medium and significant after sensitivity analyses removing non-randomised trials.